2010
DOI: 10.18261/issn1891-5949-2010-03-02
|View full text |Cite
|
Sign up to set email alerts
|

Student participation in higher education – A question of governance and power

Abstract: Since the end of the 1990s, students' right to participation has been enshrined in the Higher Education Act and the Higher Education Ordinance in Sweden. The work on the Bologna Process also means that matters of student participation are now of crucial interest and importance, and also that students are gaining participation both in the organisation and contents of the study programmes (Persson, 2003). However, research on student participation shows that students experience a lack of participation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Instructor partners were identified through an internal process, which included submission of a statement of interest and follow-up discussions with the StudentU team. Proposals for a so-called "Learning Evolution Project" (LEP) could come from any discipline, but the main theme had to be related to student participation (Bartley, Dimenäs and Hallnäs 2009). The scope of the LEPs varied, from large redesigns of degree programs to small, single module interventions.…”
Section: Project Description: Students' Universitymentioning
confidence: 99%
“…Instructor partners were identified through an internal process, which included submission of a statement of interest and follow-up discussions with the StudentU team. Proposals for a so-called "Learning Evolution Project" (LEP) could come from any discipline, but the main theme had to be related to student participation (Bartley, Dimenäs and Hallnäs 2009). The scope of the LEPs varied, from large redesigns of degree programs to small, single module interventions.…”
Section: Project Description: Students' Universitymentioning
confidence: 99%
“…A study by Sariefe and Klose found that 80.2% of students agreed that in-class participation allows them to achieve learning [4]. Student participation is "participation that entails a fair chance to influence the students' study situation and experience involvement" [5]. For example, students are involved in a decision making on the teaching and learning process [5].…”
Section: Introductionmentioning
confidence: 99%
“…Student participation is "participation that entails a fair chance to influence the students' study situation and experience involvement" [5]. For example, students are involved in a decision making on the teaching and learning process [5]. Student participation can be either on-site or online [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation